PPPU BULETIN : Special Edition Asasi Eco Ambassador - Mohamad Fhaizal, Mohamad Bukhori; Maybelline Goh, Boon Ling; Norfarahin, Norwen; Mohd Ridwan, Abd Rahman; Muhamad Ikhwan, Idris; Rohaiza, Daud; Christharina, S Gintoron; Roberta Chaya Tawie, Tingga; Mohd Aminudin, Mustapha; Mohamad Razif, Othman (Universiti Malaysia Sarawak (UNIMAS), 2022)
This publication will both encourage the students to continue spending the commitment of academic production and inspire juniors to follow their example. As in the past years, the write-up has demonstrated the wide variations of biodiversity, ecology, and environment study in various location of national park in Kuching, however, in this issue, you will find the study conducted within the campus area. Nevertheless, the study as far-ranging and divergent as eco-based potential plant for commercial uses, documentation of water quality, rapid wildlife survey, observation of plant-animal interaction, plant-plant interaction, fungi, gymnosperms, angiosperms, pteridophytes, Nepenthes, horticulture plant, palm species, medicinal plants, potential threat to ecosystem, and peat-swamp ecosystem. In a word, there is something for all the students.